Mountain Ultramarathon Induces Early Increases of Muscle Damage, Inflammation, and Risk for Acute Renal Injury - Belli, Taisa; Macedo, Denise Vaz; de Araújo, Gustavo Gomes; dos Reis, Ivan Gustavo Masselli; Scariot, Pedro Paulo Menezes; Lazarim, Fernanda Lorenzi; Nunes, Lázaro Alessandro Soares; Brenzikofer, René; Gobatto, Claudio Alexandre (Frontiers in Physiology, 2018)
Purpose: This study aimed to investigate changes in muscle damage during the course of a 217-km mountain ultramarathon (MUM). In an integrative perspective, inflammatory response and renal function were also studied. Methods: Six male ultra-runners were tested four times: pre-race, at 84-km, at 177-km, and immediately after the race. Blood samples were analyzed for serum muscle enzymes, acute-phase protein, cortisol, and renal function biomarkers. Results: Serum creatine kinase, lactate dehydrogenase, and aspartate aminotransferase increased significantly throughout the race (P < 0.001, P< 0.001; P = 0.002, respectively), and effect size (ES) denoted a large magnitude of muscle damage. These enzymes increased from pre-race (132 ± 18, 371 ± 66, and 28 ± 3 U/L, respectively) to 84-km (30, 1.8, 3.9-fold, respectively); further increased from 84-km to 177-km (4.6, 2.9, 6.1-fold, respectively); followed by a stable phase until the finish line. Regarding the inflammatory response, significant differences were found for C-reactive protein (CRP) (P < 0.001) and cortisol (P < 0.001). CRP increased from pre-race (0.9 ± 0.3 mg/L) to 177-km (243-fold), cortisol increased from pre-race (257 ± 30mmol/L) to the 84-km (2.9-fold), and both remained augmented until the finish line. Significant changes were observed for creatinine (P = 0.03), urea (P = 0.001), and glomerular filtration rate (GFR) (P < 0.001), and ES confirmed a moderate magnitude of changes in renal function biomarkers. Creatinine and urea increased, and GFR decreased from pre-race (1.00 ± 0.03 mg/dL, 33 ± 6 mg/dL, and 89 ± 5 ml/min/1.73 m2, respectively) to 84-km (1.3, 3.5, 0.7-fold, respectively), followed by a plateau phase until the finish line. Conclusion: This study shows evidence that muscle damage biomarkers presented early peak levels and they were followed by a plateau phase during the last segment of a 217-km MUM. The acute-phase response had a similar change of muscle damage. In addition, our data showed that our volunteers meet the risk criteria for acute kidney injury from 84-km until they finished the race, without demonstrating any clinical symptomatology.